Analysis of the potential for economic growth in the non-oil and gas processing industry sector in West Java province for the 2005-2009 period - Shofwatunnida Shofwatunnida (Institute of Accounting Research and Novation (IARN), 2022)
This research is one of the efforts to find out the potential of the non-oil and gas processing industry sub-sector which has a major influence on the economic growth of the non-oil and gas processing industry sector in West Java Province during 2005-2009. This study uses data on West Java's GRDP in the non-oil and gas processing industry sector and Indonesia's GDP in the non-oil and gas processing industry sector. This thesis uses an economic basis model which is reflected in the analysis of Location Quotient (LQ) and Shift Share. And Sectoral Typology is also used which is useful for knowing the leading sub-sectors of the non-oil and gas processing industry in West Java. West Java has three basic non-oil and gas processing industries, namely the other goods industry (creative industry), the textile industry, leather goods and footwear and the transportation equipment industry. machines and equipment. And two potential industries to be developed into the base sector, namely the wood and wood goods industry and the cement and non-metal mineral goods industry, because these two industries have good growth in the Province and occupy Typology VI, which means this industry is a non-base sector, has rapid growth at the provincial level, although growth at the national level is slow, so it has the potential to be developed into a base sector